Inflammatory, endocrine and metabolic correlates of fatigue in obese children. (December 2016) - Barat, Pascal; Meiffred, Marie-Claire; Brossaud, Julie; Fuchs, Dietmar; Corcuff, Jean-Benoit; Thibault, Helene; Capuron, Lucile
Highlights: Metabolic correlates of fatigue are proposed in non-diabetic obese children. Cognitive fatigue is associated with insulin resistance. The same association is present for motivational dimension of fatigue. This last association is independent of the importance of body mass index. Abstract: Alterations in endocrine functions and low-grade systemic inflammation represent fundamental characteristics of obesity. These biological systems have been repeatedly linked to fatigue symptoms. The aim of the study was to assess the relationship between fatigue dimensions and metabolic/inflammatory markers in a sample of non-diabetic obese children. The possibility that inflammation-induced alterations in tryptophan metabolism relates to specific dimensions of fatigue was also investigated in a subsample of patients. The study was conducted in 41 obese children, median aged 12 [9–15] years, recruited in a pediatric tertiary center. Three dimensions of fatigue (e.g., general fatigue, sleep/rest, cognitive fatigue) were assessed using the Pediatric Quality of Life Inventory Multidimentional Fatigue Scale. In addition, a principal component analysis was performed to identify fatigue dimensions that were specific to the population under study. This analysis extracted five relevant dimensions corresponding respectively to concentration, energy, self-perceived cognitive efficiency, sleep/rest and motivation/anhedonia. Blood samples were collected for the measurement of inflammatory and metabolic markers, including high sensitivity C-reactive protein (hs-CRP), insulin, uricemia and glycaemia. Tryptophan, kynurenine and neopterin levels were also determined in a subsample of 17 patients. In the whole population under study, cognitive fatigue and reduced motivation/anhedonia were associated with BMI, independently of sex and age. The dimension of reduced motivation/anhedonia was associated with insulin resistance and inflammatory biomarkers. The association with insulin resistance persisted when the extent of fat mass (BMI-SDS) was taken into account. No association was found between tryptophan metabolism and specific dimensions of fatigue, but kynurenine and the kynurenine/tryptophan ratio correlated with insulin and HOMA-IR. These data indicate that insulin resistance in non diabetic obese children is associated with both cognitive fatigue and reduced motivation/anhedonia and with alterations in tryptophan metabolism. Further investigations are needed to determine whether inflammation-induced alterations in tryptophan metabolism is directly or indirectly implicated in insulin resistance and related fatigue.